Structural Study of the Interaction Between the Mitochondrial Presequence of Cytochrome c Oxidase Subunit IV and Model Membranes. Issue 5 (October 1998) - Colotto, A.; Martin, I.; Ruysschaert, J.-M.; Sen, A.; Epand, R. M.
Abstract : The structural effect of the presequence of cytochrome oxidase subunit IV (p25) on multilamellar liposomes with different lipid compositions has been investigated using X-ray diffraction and electron microscopy. The presequence causes the disordering of the liposomes containing negatively charged lipids, without destabilizing the bilayer structure or destroying the multilamellar nature of the liposomes. In the systems containing only zwitterionic lipids, a small increase in the d -spacing (lamellar stacking spacing) is observed without any disorder effect suggesting a weaker interaction of the peptide and lipid. Circular Dichroism measurements of the peptide, in the presence and absence of the different lipid systems studied, show that the secondary structure of the peptide is modulated by the lipid environment. Considerable amounts of α-helix in the presequence is only observed in the systems containing negatively charged lipids. These are the same systems for which the disordering effect is observed with X-ray diffraction. It is proposed that p25 disorders the bilayer stacking by corrugating the membranes. The results are discussed in terms of the relevance of the specific lipid properties (e.g., electric charge and ability to form inverted phases) in determining how the peptide interacts with the lipid and affects its structural organization. It is suggested that the lipid properties relevant for the disordering effect induced by the peptide are the same as those involved in the formation of contact sites between mitochondrial membranes during the import of nuclear coded proteins.